Psychometric properties of martial art kendo players: a multicultural exploratory online questionnaire survey - Spantios, Michael; Kobayashi, Kei; Murai, Toshiya; Fujiwara, Hironobu (Frontiers in Psychology, 2025)
IntroductionMind-body unity, may form through stringent exercise and focused breathing. Brief participation may increase psychometric properties combatting mental health issues. We investigated how psychometric properties manifest within kendo practitioners (KP) internationally. Do they have increased psychometric properties compared to non-practitioners (NKP) due to kendo experience; our hypothesis was that they do.MethodsThe psychiatric questionnaires were disseminated through email and social media with informed consent obtained. All self-report questionnaires had good internal reliability and consistency. The study was performed using a cross-sectional design and conducted so that participants could only move on to subsequent questions if they had provided answers for prior questions. 230 European participants, 349 Japanese participants were present throughout this study. Their group was the independent variable as participants were divided by whether they practiced kendo or not. We used multiple psychiatric questionnaires like K6 (depression), COPE (stress), CD-RISC (resilience), Rosenberg’s self-esteem scale, SOC (confidence in dealing with life) and Emotional Regulation to measure various psychometric properties. Inclusion criteria were that patients be 18 or older and do exercise at least once a week.ResultsFor statistical methods a Mann–Whitney U test, descriptive statistics, reliability analysis and post-hoc power analysis were conducted using SPSS and GPower. Significant differences between KPs and NKPs for SOC (p-value = 0.013*), CDRISC (p-value = <0.001**), K6 (p-value = 0.008**) and self-esteem (p-value = <0.001**) were noted. SOC, CDRISC and K6 were deemed significant here but not when separate analyses were conducted for European or Japanese participants. European data showed no significant difference and for Japanese data only self-esteem was significant (p-value = 0.03*).DiscussionOur results support that kendo can lead to increased psychometric properties compared to non-kendo. Result differences when split in to Japanese vs European could be attributed to cultural differences. These cultural differences could affect baseline levels of reported self-esteem within a population and could be why there was a discernible difference between Japanese and European participants. Sports lacking this mindfulness component do not provide the same prescribed benefits. However, the degree of impact pertaining to these results remains to be seen and should be further investigated before being applied in a clinical setting in the future.